152k views
0 votes
What expressions from the table are equivalent to that expression ?

What expressions from the table are equivalent to that expression ?-example-1
User Scrthq
by
5.8k points

1 Answer

4 votes

Answer:

Explanation:

11).
p^{(3)/(5)}* \sqrt[10]{p^4}

=
p^{(3* 2)/(5* 2)}* \sqrt[10]{p^4}

=
p^{(6)/(10)}* \sqrt[10]{p^4}

=
\sqrt[10]{p^(6)}*\sqrt[10]{p^4}

=
\sqrt[10]{p^(10)}

= p

Yes

12).
p^{(3)/(5)}* \sqrt[10]{p^4}=\sqrt[5]{p^3} * \sqrt[10]{p^4}

But,
\sqrt[5]{p^3} * \sqrt[10]{p^4}\\eq \sqrt[3]{p^5}* \sqrt[10]{p^4}

No

13). Since,
p^{(3)/(5)}* \sqrt[10]{p^4}=p

Simplify the given expression,


\sqrt[10]{p^{(23)/(5)}}


\sqrt[10]{p^{(23)/(5)}} =p^{(23)/(50)}

No.

14).
p^{(12)/(50)}=p^{(6)/(25)}\\eq p

No.

15).
p^(24)\\eq p

No.

User Torren
by
6.9k points